Boron nitride nanotube-mediated stimulation of cell co-culture on micro-engineered hydrogels. - Leonardo Ricotti (Public Library of Science (PLoS), 2013)
In this paper, we describe the effects of the combination of topographical, mechanical, chemical and intracellular electrical stimuli on a co-culture of fibroblasts and skeletal muscle cells. The co-culture was anisotropically grown onto an engineered micro-grooved (10 µm-wide grooves) polyacrylamide substrate, showing a precisely tuned Young's modulus (∼ 14 kPa) and a small thickness (∼ 12 µm). We enhanced the co-culture properties through intracellular stimulation produced by piezoelectric nanostructures (i.e., boron nitride nanotubes) activated by ultrasounds, thus exploiting the ability of boron nitride nanotubes to convert outer mechanical waves (such as ultrasounds) in intracellular electrical stimuli, by exploiting the direct piezoelectric effect. We demonstrated that nanotubes were internalized by muscle cells and localized in both early and late endosomes, while they were not internalized by the underneath fibroblast layer. Muscle cell differentiation benefited from the synergic combination of topographical, mechanical, chemical and nanoparticle-based stimuli, showing good myotube development and alignment towards a preferential direction, as well as high expression of genes encoding key proteins for muscle contraction (i.e., actin and myosin). We also clarified the possible role of fibroblasts in this process, highlighting their response to the above mentioned physical stimuli in terms of gene expression and cytokine production. Finally, calcium imaging-based experiments demonstrated a higher functionality of the stimulated co-cultures.